Deconstructing the dichotomies of solar photovoltaic (PV) dissemination trajectories in Ghana, Kenya and Zimbabwe from 1960s – 2007 - Bawakyillenuo, S (Elsevier, 2012)
The profuse dissemination and utilisation of solar PV technology in the world is indispensable, especially in this era of climate change. However, in the African continent, between 1960 and 2007 Kenya and Zimbabwe were among countries with the highest PV dissemination, while Ghana was among countries with the least disseminations. Analysing empirical data through the lens of the Social Construction of Technology (SCOT) theory, the article aims to uncover the drivers underpinning the disparate dissemination trends of PV in the three countries within the stated period and to tease out lessons apropos replicating the successes within Kenya and Zimbabwe in Ghana. SCOT theory is chosen because it provides an excellent framework for analysing the social shaping of PV's development and diffusion processes in these countries. This theory posits that the shape and meanings of a technology do not reside in it, but are acquired through the heterogeneity of social interactions. Findings in the paper reveal that a gamut of socio-economic and political antecedents informed the varied dissemination outcomes of the technology in these countries. Premised on these findings, the paper recommends critical steps, which Ghana needs to undertake to enhance the replication of the Kenyan and Zimbabwean PV success stories.
Keywords: PV; Dissemination; Replication